â€œANALYSING THE EFFECT OF SOCIAL MEDIA ON PURCHASE INTENTION AND BRAND ATTITUDE AS INTERVERNING VARIABLE AT MALANG STRUDELâ€ - ALFIANTO, FEBI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to analyze the influence of socialmedia on brand attitudes and purchaseintentionat Malang Strudel. The population of this study is the students of University ofBrawijaya who have ever bought the product Malang Strudel.This study uses a quantitative approach with a questionnaire to collect data. As this study is using purposive sampling, therefore 120 questionnaires that are distributed to every respondent who has ever purchased Malang Strudel product. Partial Least Square (PLS) analysis is applied to analyze data using outer model and inner model.The results of this study indicate that social media provide a significant influence on consumer purchase intentions. And also consumer brand attitude both negative and positive can affect the Purchase Intention.Â Keywords: Social Media, Brand Attitude, Purchase Intention, Malang Strudel